2013
DOI: 10.1097/nmd.0b013e3182a21471
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Difficulty Discarding

Abstract: Objectives This study presents nationally representative data on the prevalence and correlates of difficulty discarding, a behavior described in many psychiatric disorders, including a new diagnosis in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, called hoarding disorder. Methods Data were derived from the National Epidemiologic Survey on Alcohol and Related Conditions, a national sample of the U.S. population (n= 43,093). Difficulty discarding worn-out/worthless items (assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Studies examined comorbidity associated with many specific symptoms: anhedonia [150], social isolation [151], panic attacks [152], hoarding [153], hazardous alcohol use [154], impulsivity [155], lack of remorse [156], shoplifting [157], firesetting [158], cruelty to animals [159], violent behaviors [160], nicotine withdrawal [161], and other symptoms or behaviors [162-166]. Participants with suicidality (ideation/behavior) had greater comorbidity than others [166-185], as did smokers [69,161,170,179,186-200] and those who used alcohol/drugs to ameliorate mood/or feel better (self-medication) [201-209].…”
Section: Major Findingsmentioning
confidence: 99%
“…Studies examined comorbidity associated with many specific symptoms: anhedonia [150], social isolation [151], panic attacks [152], hoarding [153], hazardous alcohol use [154], impulsivity [155], lack of remorse [156], shoplifting [157], firesetting [158], cruelty to animals [159], violent behaviors [160], nicotine withdrawal [161], and other symptoms or behaviors [162-166]. Participants with suicidality (ideation/behavior) had greater comorbidity than others [166-185], as did smokers [69,161,170,179,186-200] and those who used alcohol/drugs to ameliorate mood/or feel better (self-medication) [201-209].…”
Section: Major Findingsmentioning
confidence: 99%
“…14 AD affects both genders and is associated with substantial adversities, but, some research suggests a higher incidence in men. 12,15 It can be observed in different cultures and with varying age for onset of signs and symptoms. The estimated prevalence is 2% to 6% in the general population, presenting greater severity in the elderly.…”
Section:  Epidemiology and Impact Of Public Healthmentioning
confidence: 99%
“…18 Research has concluded that the accumulation behavior is a diagnosis whose course may occur concomitantly with other mental disorders, such as Personality Disorder, Generalized Anxiety Disorder, Depression, Dementia, Schizophrenia, OCD, Bipolar Mood Disorder, Social Phobia, among others. 12,15 Until inclusion in DSM-5, accumulation symptoms were often classified as a spectrum of OCD. The expressed cognitions of many individuals who accumulate could be understood as obsessions characterized by a fear of losing things and compulsions to acquire and store objects.…”
Section:  Identification Of the Accumulation Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…The primary symptoms of hoarding disorder (HD) -acquiring, clutter, and difficulty discarding -are strongly associated with severe psychiatric and psychosocial dysfunction (Rodriguez et al 2013;Samuels et al 2008;Tolin et al 2008), and are surprisingly prevalent -estimated between 2.3 % -6 % of the population (Bulli et al 2013;Iervolino et al 2009;Mueller et al 2009;Timpano et al 2011). Cognitive behaviour therapy (CBT) for hoarding is empirically successful but resource-intensive and inconsistent in efficacy , and evidence for pharmacotherapy is nascent (Saxena 2011;Saxena and Sumner 2014).…”
mentioning
confidence: 99%